2007
DOI: 10.1007/s11805-007-0405-0
|View full text |Cite
|
Sign up to set email alerts
|

Atypical endometriosis: a clinicopathologic study of 163 cases

Abstract: OBJECTIVE To investigate the clinicopathologic features of atypical endometriosis (AEM), and to discuss the relations between AEMs and tumors. METHODS A retrospective analysis was performed on 163 cases of AEMs. The changes in the glandular epithelium, stroma, and their background and the relationship with coexisting tumors were observed. RESULTS The AEMs account of for 4.4% (163/3,724) of the endometriosis (EM) cases. Of 172 AEM foci of 163 patients, 168 were in the ovary, and the other 4 were in the fallopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(23 reference statements)
2
3
0
Order By: Relevance
“…In this study, we report 36 cases of A-EMS and expand the morphologic, immunohistochemical, and molecular understanding of this atypical lesion. A-EMS is described as a rare phenomenon, comprising 1.7% to 4.4% of all endometriotic lesions (5,6,9). Our data appears to be similar, since cases evaluated represent <1% of all EMS cases reported over an…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, we report 36 cases of A-EMS and expand the morphologic, immunohistochemical, and molecular understanding of this atypical lesion. A-EMS is described as a rare phenomenon, comprising 1.7% to 4.4% of all endometriotic lesions (5,6,9). Our data appears to be similar, since cases evaluated represent <1% of all EMS cases reported over an…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we report 36 cases of A-EMS and expand the morphologic, immunohistochemical, and molecular understanding of this atypical lesion. A-EMS is described as a rare phenomenon, comprising 1.7% to 4.4% of all endometriotic lesions 5,6,9 . Our data appears to be similar, since cases evaluated represent <1% of all EMS cases reported over an 11-yr period (although not all cases were retrospectively evaluated for the presence of atypical features, and we relied on the description of atypia in the report for identification of E-AMS cases).…”
Section: Discussionsupporting
confidence: 55%
“…In recent years, it has been reported that atypical endometriosis occurs in up to 6.8% of the cases of ovarian cancer, and ovarian endometrioid carcinomas occurring with endometriosis have more atypical changes. 3 Malignant transformation of endometriosis is becoming an important concern in the field of gynecology. Compared with benign ovarian endometriosis, alteration of molecular proteins has been reported in endometriosis-associated ovarian carcinoma (EAOC), such as estrogen receptors (ERs), progesterone receptors, phosphatase and tensin homolog, 4 P53, and bcl-2 protein.…”
mentioning
confidence: 99%
“…Molecular and epidemiological studies have also provided a strong association between atypical endometriosis and ovarian cancer [ 1 , 2 ]. It has been reported that atypical endometriosis occurs in up to 6.8% of ovarian cancer cases, and ovarian endometrioid carcinoma originating from ectopic endometrium is more prone to atypical changes [ 3 ]. These factors, therefore, demonstrate a high risk of type I ovarian cancer in women with these atypical cells and/or the structure of ovarian endometriosis.…”
Section: Introductionmentioning
confidence: 99%